Antigiardial Activity of Foeniculum vulgare Hexane Extract and Some of Its Constituents - Irma G. Domínguez-Vigil; Benito D. Mata-Cárdenas; Patricia C. Esquivel-Ferriño; Francisco G. Avalos-Alanís; Javier Vargas-Villarreal; María del Rayo Camacho-Corona (Plants, 2022)
Foeniculum vulgare is used for the treatment of diarrhea in Mexican traditional medicine. Hexane extract showed 94 % inhibition of Giardia duodenalis trophozoites at 300 μg/mL. Therefore, 20 constituents of hexane extract were evaluated to determine their antigiardial activity. Interestingly, six compounds showed good activity toward the parasite. These compounds were (1R,4S) (+)-Camphene (61%), (R)(−)-Carvone (66%), estragole (49%), p-anisaldehyde (67%), 1,3-benzenediol (56%), and trans, trans-2,4-undecadienal (97%). The aldehyde trans, trans-2,4-undecadienal was the most active compound with an IC50 value of 72.11 µg/mL against G. duodenalis trophozoites. This aldehyde was less toxic (IC50 588.8 µg/mL) than positive control metronidazole (IC50 83.5 µg/mL) against Vero cells. The above results could support the use of F. vulgare in Mexican traditional medicine.